Analisis Pengaruh Rasio Keuangan terhadap Pertumbuhan Laba pada PT. Univista Utama Medan - Vivian Diaphenia; Thomas Sumarsan Goh; Elidawati Elidawati; Edison Sagala (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2023)
The purpose of this study was to determine the effect of financial ratios consistingof 5 (five) financial ratios namely Cash Ratio, Primary Ratio, Gross Profit Margin,level of sales and Total Asset Turnover on Profit Growth at PT. Main University.The method used is quantitative research. The population in this study is thefinancial statements of PT. Main Univista for 3 years for the 2018-2020 period,while the sample in this study was 36 data. The analysis model in this study ismultiple linear regression using the SPSS program. Data testing was carried outusing the classical assumption test, the coefficient of determination test, the F testand the t test. The conclusion from the results of this study is that Cash Ratio andTotal Assets turnover partially have a significant effect on profit growth at PTUnivista Utama, Primary Ratio, Gross Profit Margin and sales level partially haveno effect on profit growth at PT Univista Utama. Cash Ratio, Total Assets turn,Primary Ratio, Gross Profit Margin and sales level simultaneously affect profitgrowth at PT Univista Utama.